Genistein Ameliorates Scopolamine-Induced Amnesia in Mice Through the Regulation of the Cholinergic Neurotransmission, Antioxidant System and the ERK/CREB/BDNF Signaling - Lu, Cong; Wang, Yan; Xu, Teng; Li, Qi; Wang, Donghui; Zhang, Lijing; Fan, Bei; Wang, Fengzhong; Liu, Xinmin (Frontiers in Pharmacology, 2018)
Genistein (GE) was found to exert a wide spectrum of biological activities, including antioxidant, anti-inflammatory, anti-mutagenic, anticancer, and cardio-protective effects. In addition, both clinical and preclinical studies have recently suggested GE a potential neuroprotective and memory-enhancing drug against neurodegenerative diseases. The animal model of scopolamine (Scop)-induced amnesia is widely used to study underlying mechanisms and treatment of cognitive impairment in neurodegenerative diseases. However, there is no report about the effects of GE on scopolamine (Scop)-induced amnesia in mice. Therefore, the present study was carried out to investigate the beneficial effects and potential mechanism of GE against Scop-induced deficits in mice. The mice were orally pretreated with GE (10, 20 and 40 mg/kg) and donepezil (1.60 mg/kg) for 14 days. After the pretreatment, the open field test was conducted to assess the effect of GE on the locomotor activity of mice. Thereafter, mice were daily injected with Scop (0.75 mg/kg) intraperitoneally to induce memory deficits and subjected to the cognitive behavioral tests including the object location recognition (OLR) experiment and Morris water maze (MWM) task. After the behavioral tests, biochemical parameter assay and western blot analysis were used to examine the underlying mechanisms of its action. The results showed that GE administration significantly improved the cognitive performance of Scop-treated mice in object location recognition and Morris water maze tests, exerting the memory-enhancing effects. Additionally, GE remarkably promoted the cholinergic neurotransmission and protected against the oxidative stress damage in the hippocampus of Scop-treated mice, as indicted by decreasing AChE activity, elevating ChAT activity and Ach level, increasing SOD activity, lowering the level of MDA and increasing GSH content. Furthermore, GE was found to significantly upregulate the expression levels of p-ERK, p-CREB and BDNF proteins in the hippocampus of Scop-treated mice. Taken together, these results for the first time found that Genistein exerts cognitive-improving effects in Scop-induced amnesia and suggested it may be a promising candidate compound for the prevention against some neurodegenerative diseases such as Alzheimer's disease (AD).